Max Ride Autoshop N’ Customs / Mohd Izzat Johari... [et al.] - Johari, Mohd Izzat; Ahmad Tarmizi, Mohd Nizam; Abd Malek, Syahril Amri; Azizal, Muhammad Firdaus (2007)
MAX RIDE AUTOSHOP N' CUSTOMS is a new company that doing the business selling car accessories and to custom made cars from our customers. We did some research and found out that this type of business ( custom made) already started in the United State and we try to bring something different to car users in Malaysia. This company is a partnership company incorporated by five members and it means that all partners that involves must be responsible to bear all the risk happens to the company. The scope of the operation is giving our best services to the customers and to ensure that our product is in best quality that will satisfy the customers. MAX RIDE AUTOSHOP N' CUSTOMS has decided to start its operation in January 2008 at No 247 & 248 Jln Utama 4, Kompleks Perniagaan Utama Sulatanah Sambungan, 05150 Mergong, Kedah Darul Aman. The selected location is strategic and it is suitable for making business because it is found becoming the local people focus in doing their business. Furthermore, it also easy to be found and near the road which is the main road connected between Kangar and Alor Setar.